Upaya Kesejahteraan Sosial pada Penyandang Tunanetra di Panti Karya Hephata - Kirye Elisye Marsaulina Sihombing; Hairani Siregar; Berlianti Berlianti (Yayasan Literasi Sains Indonesia, 2022)
The visually impaired often experience difficulties because society's view tends to be less positive towards them. Not infrequently they are underestimated by society, family, and even themselves. The visually impaired are often seen as helpless, unable to stand up for themselves, and always willing to be helped. The community's treatment of them also tends to be merciful, which causes them to feel they don't have a place in society. This makes them tend to be insecure and limit themselves to interacting with the environment and lack the courage to do something. One of private institution that pays special attention to fulfilling the rights of the visually imppaired is Panti Karya Hephata. This research was conducted to see the social welfare efforts carried out by Panti Karya Hephata for the visually impaired. This research was conducted using a qualitative descriptive approach, with data collection techniques through in-depth interviews, observation, and literature study. Based on the research that has been done, the social welfare efforts carried out by Panti Karya Hephata for the visually impaired are through self-development programs, formal education, work development, and mental-spiritual development.